Hubungan Karakteristik Penyandang DM TIPE II dengan Efikasi Diri : Literature Review - Hikmah, Fifi Nur; Clara, Hertuida (Neolectura, 2025)
Diabetes Mellitus (DM) is the 6th highest metabolic disease in Indonesia caused by insulin resistance. The risk of complications from DM includes microvascular and macrovascular. Therefore, efforts to prevent complications are to implement regular diabetes self-management such as diet, exercise, glucose monitoring, therapy, education, and foot care. Self-efficacy is a factor that can influence self-care where the characteristics of individuals with DM may also influence self-efficacy such as age, gender, education, knowledge, and duration of DM. Objective: from this study to analyze the relationship between the characteristics of people with type II DM and self-efficac. Cross-sectional approach keywords DM Type 2, demographics, and self-efficacy. Selected articles from 2020–2024. Article search was conducted using Google Scholar. Results: Based on the results of the literature review, there is a significant relationship between the duration of DM and knowledge with self-efficacy of people with DM type 2, but there is no relationship between age, gender and education level with self-efficacy. Based on the results of the literature review, there is a significant relationship between the length of time suffering from DM and knowledge with self-efficacy of people with type 2 DM, but there is no relationship between age, gender and level of education with self-efficacy. The factors most related to self-efficacy are the length of time suffering from DM and knowledge of DM.